Methodological provision of determining individual typology peculiarities in winterers concerning the adaptation to extreme conditions of life activity - Miroshnychenko, Olena; VoznyukОleksander; KryvonosОleksander (Ukrainian Antarctic Journal, 2025)
The prospects for international cooperation between Ukraine and the countries of the Antarctic Treaty depend on the level of professional training of specialists who carry out professional activities in the harsh conditions of Antarctica. The purpose of the article is to substantiate the feasibility of using psychological methods for studying the individual typological characteristics of winterers in terms of adaptation to extreme living/working conditions. The tasks of the research are to provide a description of the authors’ methodology for determining the character types of winterers and to prove the effectiveness of implementing the methodology in the psychological selection of participants for Antarctic expeditions. The study was conducted at the National Antarctic Scientific Center of the Ministry of Education and Science of Ukraine, Kyiv and at the Akademik Vernadsky station. The sample consisted of 71 winterers of ten Ukrainian Antarctic expeditions, the age of the subjects varied from 22 to 64 years. Measurements of the adaptation component indicators within the methodology for determining the character types of winterers were made due to online testing platform. The research enables to identify 12 psychological types of character (persistent-distrustful, authoritarian, demonstrative, hyperthymic, withdrawn-introverted, conscientious-pedantic, emotional, dysthymic, conformal, anxious, unstable, labile). Each of the 12 types of character has been described with outlining a set of psychological traits that are to be put into consideration while analysing the winterers’ adaptation to extreme conditions of Antarctica. The conclusion has been made, which with certain in-depth studies may acquire a level of psychological regularity: the representatives of different character types characterised by different strength of nervous processes (hyperthymic and authoritarian) adapt to extreme conditions in opposite ways, when the action of extreme factors has an opposite effect on representatives of these character types. So, the influence of extreme factors on representatives of the hyperthymic type reduces their adaptive capabilities, and this influence on representatives of the authoritarian type increases their adaptive capabilities.